KARY I ODZNACZENIA W RZYMSKIM PRAWIE WOJSKOWYM - Szeląg, Tomasz (Zeszyty Prawnicze, 2017)
Punishments and Rewards in the Roman Military Law Summary First part of the article presents an analysis of punishments in the Roman military law. The punishments may be divided into five following categories: a) material punishments as depravation of pay; b) reduction; c) disgrace; d) corporal punishments; e) death penalty. The second part carries a description of the rewards, that soldiers or commanders may achieve. I have analysed herein such kinds of rewards as decorations, material rewards, promotion, a Triumph and an ovation.